Effects of bioplus 2B and Levucell SB on weanling pig growth performance and fecal shedding in response to oral challenge with salmonella serovar typhimurium - Barker, M.R.; Nietfeld, Jerome C.; Minton, J. Ernest; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Eighty-five pigs (initially 12.9 lb and 15 ±1 d of age) were used in two 28-d trials to determine the effects of the probiotics BioPlus 2B (a bacillus-based product from Chr. Hansen BioSystems), a source of Bacillus subtilis and Bacillus licheniformis, and Levucell SB (an active dry yeast product from Lallemand Animal Nutrition), a yeast (Saccharomyces cerevisiae) product that is a source of mannanoligosaccharides on growth and performance of Salmonella enterica serovar Typhimurium shedding in a young growing pig model. Pigs were fed one of five dietary treatments: 1) A control diet containing no probiotics or antibiotics; 2) the control diet with carbadox (50 g/ton); 3) the control diet with Bio-Plus 2B (0.05% of the diet); 4) the control diet with Levucell SB (100 g/ton); 5) the control diet with Bioplus 2B (0.05% of the diet) and Levucell SB (100 g/ton). Diets did not contain growth promoting levels of zinc oxide or copper sulfate. Significant differences in the two trials were seen, with the second trial having 0.1 lb/d greater growth and .18 lb/d greater feed intake than the first trial. In trial 1, pigs fed the control diet and Bioplus 2B had greater gains and feed intakes (P<0.05 and P<0.02 respectively) than those fed carbadox. In trial two, pigs fed carbadox had better performance than those fed the control and combination diets, with the BioPlus 2B and Levucell SB treatments having intermediate growth and feed intake. Fecal shedding rates of salmonella were not different (P>0.10) between diets. Results indicate that within an environment where enteric disease may be active, BioPlus 2B and Levucell SB may provide growth enhancement over a diet devoid of antimicrobials.
Keywords: Weanling pigs; Disease challenge; Salmonella; BioPlus 2B; Saccharomyces cerevisiae; Swine